Produksi dan Pengukuran Aktivitas Protease dari Isolat Bakteri BKL-1 dan BKU-31 - Wiwit Artika (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2010)
BKL-1 and BKU-31 bacteria isolates were collected from digestive tract of kerapu lumpur (Epinephelus tauvina) and identified as Serratia marcescens biogp 1 dan Serratia marcescens respectively. BKL-1 crude protease were obtained after 27 hours incubation period in Nutrient Broth (NB) medium added with peptone 0.5%, NaCl 0.5%, lactose 0.1%, and CaCl2 0.1%. BKU-31 crude proteases were obtained in NB medium added with 0.1% skimmed milk (NBS) for 18 hours incubation period. The highest activity of proteases of S. marcescens biogp 1 BKL-1 reached after 27 hours of incubation, namely 0.002 U/ml with protein concentration 0.064 mg/ml. The proteases of S. marcescens BKU-31, on the other hand, reached their highest activity (0.064 U/ml) at 24 hours of incubation with protein concentration 0.056 mg/ml.The optimum temperature crude BKL-1 proteases were 30°C, whereas BKU-31 proteasess had the optimum temperature of 50 ºC.